DEVELOPING ADVENTURE TOURISM IN BANGLADESH : Case study: Cox´s Bazar and Saint Martin Island - Ahammed, Md.tanbir (Centria-ammattikorkeakoulu (Keski-Pohjanmaan ammattikorkeakoulu), 2015)
Cox´s Bazar and the Saint Martin Island are located in the southern parts of Bangladesh, known as the most beautiful places in the country. For many years, it has been a general holiday destination for tourists from all over the world. Blessed with the longest uninterrupted sea beach and overlooking the Myanmar border, it has many resources that can be ideal for developing adventure tourism. The purpose of this thesis was to find out possible development for adventure tourism in Cox´s Bazar and Saint Martin Island. This thesis was divided into two parts, the first part was a theoretical part and deals with required development theories for developments and for the second part, the qualitative research method was used to achieve the results, using semi-structured interviews, which includes questions about Cox´s Bazar and Saint Martin Island for developing adventure tourism then the text was analysed. Various books, journals and website information were used for the theoretical part, which provided an overall condition of the existing tourism market and necessary steps that should be taken in order to develop adventure tourism. The result of the research has accumulated many important answers. Data acquired through interviews on the subjects of Cox´s Bazar and Saint Martin Island expressed the relation between proper marketing and destination development and necessary steps to overcome the challenges for developing adventure tourism and to make Cox´s Bazar and Saint Martin Island into major adventure tourism destinations were also provided.